1. /
2. CBSE
3. /
4. Class 12
5. /
6. Mathematics
7. /
8. Class 12 Maths Application...

# Class 12 Maths Application of Derivatives Extra Questions

### myCBSEguide App

Download the app to get CBSE Sample Papers 2023-24, NCERT Solutions (Revised), Most Important Questions, Previous Year Question Bank, Mock Tests, and Detailed Notes.

Class 12 Maths Application of Derivatives Extra Questions. myCBSEguide has just released Chapter Wise Question Answers for class 12 Maths. There chapter wise Practice Questions with complete solutions are available for download in myCBSEguide website and mobile app. These Questions with solution are prepared by our team of expert teachers who are teaching grade in CBSE schools for years. There are around 4-5 set of solved Chapter 6 Application of Derivatives Mathematics Extra Questions from each and every chapter. The students will not miss any concept in these Chapter wise question that are specially designed to tackle Board Exam. We have taken care of every single concept given in CBSE Class 12 Mathematics syllabus and questions are framed as per the latest marking scheme and blue print issued by CBSE for class 12.

Class 12 Chapter 6 Maths Extra Questions

## Application of Derivatives Chapter 6 Important Questions

Chapter 6 Application of Derivatives

1. The instantaneous rate of change at t = 1 for the function f (t) =te-t + 9 is
1. 2
2. 9
3. -1
4. -0
2. The function f (x) = x2, for all real x, is
1. Neither decreasing nor increasing
2. Increasing
3. Decreasing
4. None of these
3. The slope of the tangent to the curve x = a sint, y = a {tex}\left\{ {\cos t + \log (\tan \frac{t}{2})} \right\}{/tex} at the point ‘t’ is

1. {tex}\tan \frac{t}{2}{/tex}
2. none of these
3. tan t
4. cot t
4. The function f (x) = x2 – 2x is strict decreasing in the interval

1. none of these
2. R
3. {tex} [1,\infty ) {/tex}
4. {tex} ({\text{ }}-\infty ,{\text{ }}1){/tex}
5. The equation of the tangent to the curve y2 = 4ax at the point (at2, 2at) is

1. ty = x + at2
2. none of these
3. tx + y =at3
4. ty = x – at2
6. The maximum value of {tex}{\left( {\frac{1}{x}} \right)^x}{/tex} is ________.
7. The minimum value of f if f(x) = sin x in [{tex}\frac {-\pi}2,\frac {\pi}2{/tex}] is ________.
8. The equation of normal to the curve y = tan x at (0, 0) is ________.
9. Find the approximate value of f(3.02) where f(x) = 3x2 + 5x + 3.

10. If the line ax+by+c=0 is a normal to the curve xy=1,then show that either a>0,b<0 or a<0,b>0

11. Find the interval in which the function f(x) = x2e-x is increasing.

12. The volume of a sphere is increasing at the rate of 3 cubic centimeter per second. Find the rate of increase of its surface area, when the radius is 2 cm.

13. Find the approximate value of {tex}{\left( {1.999} \right)^5}{/tex}.

14. Show that the function f(x) = 4x3 – 18x2 + 27x – 7 is always increasing on R.

15. Show that the height of the cylinder of maximum volume that can be inscribed in a sphere of radius a is {tex}\frac{{2a}}{{\sqrt 3 }}{/tex}.

16. A particle moves along the curve 6y = x3 + 2. Find the points on the curve at which the y-coordinate is changing 8 times as fast as the x – coordinate.

17. Find the equation of tangent to the curve {tex} y = \frac { x – 7 } { x ^ { 2 } – 5 x + 6 }{/tex} at the point, where it cuts the X-axis.

18. Show that semi – vertical angle of right circular cone of given surface area and maximum volume is {tex}{\sin ^{ – 1}}\left( {\frac{1}{3}} \right){/tex}.

Chapter 6 Application of Derivatives

Solution

1. (d) 0, Explanation: {tex}f'(t) = t{e^{ – t}}( – 1) + {e^{ – t}} \Rightarrow f'(1) = – {e^{ – 1}} + {e^{ – 1}} = 0 {/tex}
2. (a) Neither decreasing nor increasing, Explanation: f(x) = x2
{tex}\Rightarrow {/tex} f'(x) = 2x for all x in R.
Since f ‘(x) = 2x > 0 for x >0, and f ‘ (x) = 2x< 0 for x < 0, therefore on R, f is neither increasing nor decreasing. Infact , f is strict increasing on [ 0,{tex}\infty {/tex} ) and strict decreasing on (- {tex}\infty ,0\;{/tex}].
3. (d) cot t, Explanation: Given, {tex} x=asint,y=a\left\{ { \cos t+\log (\tan \frac { t }{ 2 } ) } \right\}{/tex}
{tex} { { dx } }{ { dt } } =a\cos t,\frac { { dy } }{ { dt } } {/tex}{tex}=a\left[ -\sin t+\frac { 1 }{ \tan \frac { t }{ 2 } } .{ sec }^{ 2 }\frac { t }{ 2 } .\frac { 1 }{ 2 } \right] {/tex}{tex}=a\left[ -\sin t+\frac { 1 }{ 2sin\frac { t }{ 2 } .cos\frac { t }{ 2 } } \right] {/tex}{tex}=a\left[ -\sin t+\frac { 1 }{ sint } \right] =a\frac { { cos }^{ 2 }t }{ sint } {/tex}
Slope of the tangent{tex}=\frac { { dy } }{ { dx } } =\frac { { \frac { { dy } }{ { dt } } } }{ { \frac { { dx } }{ { dt } } } } =\frac { { a\frac { { cos }^{ 2 }t }{ sint } } }{ { a\cos t } } =\cot t{/tex}
4. (d) {tex} ({\text{ }}-\infty ,{\text{ }}1){/tex}Explanation: f ‘ (x ) = 2x – 2 = 2 ( x – 1) <0 if x < 1 i.e. x {tex}x \in \left( { – \infty ,1} \right) {/tex}. Hence f is strict decreasing in{tex}\left( { – \infty ,1} \right){/tex}
5. (a) ty = x +at2Explanation: {tex}{ y }^{ 2 }=4ax{/tex}
{tex}\\ \Rightarrow 2y\frac { dy }{ dx } =4a{/tex}
{tex}\\ \Rightarrow \frac { { dy } }{ { dx } } =\frac { 2a }{ y }{/tex}
{tex} \Rightarrow \frac { { dy } }{ { dx } } {/tex} at {tex}(a{ t^{ 2 } },2at){/tex} is {tex}\frac { { 2a } }{ { 2at } } =\frac { 1 }{ t } {/tex}
{tex}\Rightarrow {/tex} Slope of tangent {tex}=m=\frac { 1 }{ t } {/tex}
Hence, equation of tangent is {tex} y-{ y }_{ 1 }=m\left( x-{ x }_{ 1 } \right) {/tex}
{tex}\\ \Rightarrow y-2at=\frac { 1 }{ t } (x-a{ t^{ 2 } }){/tex}
{tex}\Rightarrow yt-2a{ t^{ 2 } }=x-a{ t^{ 2 } }{/tex}
{tex}\Rightarrow yt=x+a{ t^{ 2 } }{/tex}
6. {tex}{e^{\frac{1}{e}}}{/tex}
7. -1
8. x + y = 0
9. {tex}x = 3,\Delta x = 0.02{/tex}
{tex}f(x + \Delta x) = f(x) + f'(x)\Delta x{/tex}
{tex}f(x + \Delta x) = (3{x^2} + 5x + 3) + (6x + 5) \times 0.02{/tex}
Put {tex}x = 3,\Delta x = 0.02{/tex}
f(3.02)={3(9)+5(3)+3}+{6(3)+5}×0.02 =45+0.46
f(3.02) = 45.46
10. we have, xy =1
{tex} \Rightarrow y = \frac{1}{x}{/tex}
{tex}\therefore\ \frac{dy}{dx}=-\frac{1}{x^2}{/tex}
The slope of the normal = x2
If ax+by+c=0 is normal to the curve xy=1,then
{tex}x^2=-\frac{a}{b} \ [\because slope\ of\ normal\ =-\frac{coeff.\ of\ x}{coeff. of\ y}]{/tex}
{tex}\therefore \; – \frac{a}{b} > 0{/tex}
{tex}\Rightarrow\ a>0,b<0 \ or\ a<0,b>0{/tex}
11. f(x) = x2e-x
Differentiating w.r.t x, we get,
f'(x) = {tex}-x^2e^{-x}+2xe^{-x}=xe^{-x}(2-x){/tex}
For increasing function, f'(x){tex}\geq0{/tex}
{tex}xe^{-x}(2-x)\geq0{/tex}
{tex}x(2-x)\geq0{/tex} [{tex}\because\ e^{-x}{/tex} is always positive] {tex}x(x-2)\leq0{/tex} [ since – ( x – 2) will change the inequality )
Here x < 0 & (x – 2) > 0 {tex}\Rightarrow{/tex} x < 0 & x > 2 {tex}\Rightarrow{/tex} 0 < x < 2
But when x > 0 & (x – 2) < 0 {tex}\Rightarrow{/tex} x > 0 & x < 2
{tex}0\le x \leq\ 2{/tex}
12. Let r be the radius of sphere and V be its volume.
Then V = {tex}\frac { 4 } { 3 } \pi r ^ { 3 }{/tex}……..(i)
Given, {tex}\frac { d V } { d t }{/tex} = 3 cm3/s
Differentiating (i) both sides w.r.t x,we get,
{tex}\frac { d V } { d t } = \frac { 4 } { 3 } \pi \left( 3 r ^ { 2 } \right) \frac { d r } { d t }{/tex}
{tex}\Rightarrow \quad 3 = \frac { 4 } { 3 } ( 3 \pi r ^2 ) \frac { d r } { d t }{/tex}
{tex}\Rightarrow \quad \frac { d r } { d t } = \frac { 3 } { 4 \pi r ^ { 2 } }{/tex}…….(ii)
Now, let S be the surface area of sphere, then S = {tex}4 \pi r ^ { 2 }{/tex}
{tex}\Rightarrow \quad \frac { d S } { d t } = 4 \pi ( 2 r ) \frac { d r } { d t }{/tex}
{tex}\Rightarrow \quad \frac { d S } { d t } = 8 \pi r \left( \frac { 3 } { 4 \pi r ^ { 2 } } \right){/tex}[using Eq.(ii)] {tex}\Rightarrow \quad \left( \frac { d S } { d t } \right) = \frac { 6 } { r }{/tex}
when r = 2, then {tex}\frac { d S } { d t } = \frac { 6 } { 2 }{/tex} = 3 cm2/s
Therefore,the rate of inrcrease of the surface area of sphere is 3 cm{tex}^2{/tex}/s when it’s radius is 2 cm
13. Let x = 2
and {tex}\Delta x = – 0.001\,\left[ {\because 2 – 0.001 = 1.999} \right]{/tex}
let y = x5
On differentiating both sides w.r.t. x, we get
{tex}\frac{{dy}}{{dx}} = 5{x^4}{/tex}
Now, {tex}\Delta y = \frac{{dy}}{{dx}}.\Delta x = 5{x^4} \times \Delta x{/tex}
{tex} = 5 \times {2^4} \times \left[ { – 0.001} \right]{/tex}
{tex} = – 80 \times 0.001 = – 0.080{/tex}
{tex}\therefore {\left( {1.999} \right)^5} = y + \Delta y{/tex}
{tex}= {2^5} + \left( { – 0.080} \right){/tex}
= 32 – 0.080 = 31.920
14. Here, f(x) =4x3 – 18x2 + 27x – 7
On differentiating both sides w.r.t. x, we get
f'(x) = 12x2 – 36x + 27
{tex}\Rightarrow{/tex}f'(x) = 3(4x2 -12 + 9)
{tex}\Rightarrow{/tex} f'(x) = 3(x – 3)2
{tex}\Rightarrow{/tex} f'(x) {tex}\geq{/tex} 0
Since, a perfect square number cannot be negative] {tex}\therefore{/tex} Given function f(x) is an increasing function on R.

15. {tex}v = \pi {r^2}.2x\,\,\left[ \begin{gathered} \because OL = x \hfill \\ LM = 2x \hfill \\ \end{gathered} \right]{/tex}
{tex} = \pi .\left( {{a^2} – {x^2}} \right).2x{/tex}
{tex}V = 2\pi \left( {{a^2}x – {x^3}} \right){/tex}
{tex}\frac{{dv}}{{dx}} = 2\pi \left( {{a^2} – 3{x^2}} \right){/tex}
{tex}\frac{{{d^2}v}}{{d{x^2}}} = 2\pi \left[ {0 – 6x} \right]{/tex}
{tex} = – 12\pi x{/tex}
For maximum/minimum
{tex}\frac{{dv}}{{dx}} = 0{/tex}
{tex}2\pi \left[ {{a^2} – 3{x^2}} \right] = 0{/tex}
{tex}{a^2} = 3{x^2} \Rightarrow \sqrt {\frac{{{a^2}}}{3}} = x{/tex}
{tex} \Rightarrow x = \frac{a}{{\sqrt 3 }}{/tex}
{tex}{\left. {\frac{{{d^2}v}}{{d{x^2}}}} \right]_{x = \frac{a}{{\sqrt 3 }}}} = – 12\pi .\frac{a}{{\sqrt 3 }}{/tex}
= – tive maximum
Volume is maximum at {tex}x = \frac{a}{{\sqrt 3 }}{/tex}
Height of cylinder of maximum volume is
= 2x
{tex} = 2 \times \frac{a}{{\sqrt 3 }}{/tex}
{tex} = \frac{{2a}}{{\sqrt 3 }}{/tex}
16. Given curve is 6y = x3 + 2 …(i)
so, {tex}6\frac{{dy}}{{dt}} = 3{x^2}\frac{{dx}}{{dt}}{/tex}
{tex}\Rightarrow 6 \times 8\frac{{dx}}{{dt}} = 3{x^2}\frac{{dx}}{{dt}}\,\,\left[ {\because \frac{{dy}}{{dt}} = 8\frac{{dx}}{{dt}}} \right]{/tex}
{tex}\Rightarrow 16 = {x^2}{/tex}
{tex}\Rightarrow x = \pm 4{/tex}
Put the value of x in equation (1)
When x = 4
6y = ( 4 )3 + 2
{tex}\Rightarrow{/tex} 6y = 64 + 2
{tex}\Rightarrow{/tex} 6y = 66
{tex}\therefore{/tex} {tex}y = \frac{{66}}{6} = 11{/tex}
So, point is (4, 11)
Now, When x = – 4
6y = ( – 4}3 + 2
= – 64 + 2
{tex}\therefore{/tex} {tex}y = \frac{{ – 62}}{6}= \frac{-31}{3}{/tex}
So the point is {tex}\left( { – 4,\frac{{ – 31}}{3}} \right){/tex}
17. Given equation of curve is
{tex} y = \frac { x – 7 } { x ^ { 2 } – 5 x + 6 }{/tex}…….(i)
On differentiating both sides w.r.t. x, we get
{tex} \frac { d y } { d x } = \frac { \left( x ^ { 2 } – 5 x + 6 \right) \cdot 1 – ( x – 7 ) ( 2 x – 5 ) } { \left( x ^ { 2 } – 5 x + 6 \right) ^ { 2 } }{/tex}{tex}\left[ \because \frac { d } { d x } \left( \frac { u } { v } \right) = \frac { v \frac { d u } { d x } – u \frac { d v } { d x } } { v ^ { 2 } } \right]{/tex}
{tex}\Rightarrow \frac { d y } { d x } = \frac { \left[ \left( x ^ { 2 } – 5 x + 6 \right) – y \left( x ^ { 2 } – 5 x + 6 \right) (2x +5)\right] } { \left( x ^ { 2 } – 5 x + 6 \right) ^ { 2 } }{/tex}
{tex}\Rightarrow \frac { d y } { d x } = \frac { 1 – ( 2 x – 5 ) y } { x ^ { 2 } – 5 x + 6 }{/tex}[dividing numerator and denominator by x2 – 5x + 6] Also, given that curve cuts X-axis, so its y-coordinate is zero.
Put y = 0 in Eq. (i), we get
{tex}\frac { x – 7 } { x ^ { 2 } – 5 x + 6 } = 0{/tex}
{tex}\Rightarrow{/tex} x= 7
So, curve passes through the point (7, 0).
Now, slope of tangent at (7,0) is
{tex}m = \left( \frac { d y } { d x } \right) _ { ( 2,0 ) } = \frac { 1 – 0 } { 49 – 35 + 6 } = \frac { 1 } { 20 }{/tex}
Hence, the required equation of tangent passing through the point (7, 0) having slope 1/20 is
y – 0 = {tex}\frac{1}{20}{/tex}(x – 7)
{tex} \Rightarrow{/tex} 20y = x – 7
{tex} \therefore{/tex} x – 20y = 7

18. {tex}s = \pi {r^2} + \pi rl{/tex} (given)
{tex}\Rightarrow{/tex}{tex}l = \frac{{s – \pi {r^2}}}{{\pi r}}{/tex}
Let v be the volume
{tex}v = \frac{1}{3}\pi {r^2}h{/tex}
{tex}\Rightarrow{/tex}{tex}{v^2} = \frac{1}{9}{\pi ^2}{r^4}{h^2}\,\,\left[ {{h^2} = {l^2} – {r^2}} \right]{/tex}
{tex}\Rightarrow{/tex}{tex}{v^2} = \frac{1}{9}{\pi ^2}{r^4}\,\left( {{l^2} – {r^2}} \right){/tex}
{tex}\Rightarrow{/tex}{tex}{v^2} = \frac{1}{9}{\pi ^2}{r^4}\left[ {\,{{\left( {\frac{{s – \pi {r^2}}}{{\pi r}}} \right)}^2} – {r^2}} \right]{/tex}
{tex}= \frac{1}{9}{\pi ^2}{r^4}\left[ {\frac{{\left( {s – \pi {r^2}} \right)}^2}{{{\pi ^2}{r^2}}} – \frac{{{r^2}}}{1}} \right]{/tex}
{tex}= \frac{1}{9}{r^2}\left[ {{{\left( {s – \pi {r^2}} \right)}^2} – {\pi ^2}{r^4}} \right]{/tex}
{tex}= \frac{1}{9}{r^2}\left[ {{s^2} + {\pi ^2}{r^4} – 2s\pi {r^2} – {\pi ^2}{r^4}} \right]{/tex}
{tex}= \frac{1}{9}{r^2}\left[ {{s^2} – 2s\pi {r^2}} \right]{/tex}
{tex}z = \frac{1}{9}\left[ {{s^2}{r^2} – 2s\pi {r^4}} \right]{/tex}
{tex}\left[ {\because {v^2} = z} \right]{/tex}
Now {tex}\frac{{dz}}{{dr}} = \frac{1}{9}\,\left[ {2r{s^2} – 8s\pi {r^3}} \right]{/tex}
{tex}0 = \frac{1}{9}\,\left[ {2r{s^2} – 8s\pi {r^3}} \right]{/tex}
{tex}8s\pi {r^2} = 2r{s^2}{/tex}
{tex}\implies{/tex} {tex}4\pi {r^2} = s{/tex}
Now {tex}\frac{{{d^2}z}}{{d{x^2}}} = \frac{1}{9}\,\left[ {2{s^2} – 24s\pi {r^2}} \right]{/tex}
{tex}{\left. {\frac{{{d^2}z}}{{d{x^2}}}} \right]_{{r^2} = \frac{s}{{4\pi }}}} = \frac{1}{9}\,\left[ {{{25}^2} – 24\pi .\frac{5}{{4\pi }}} \right]{/tex}
= + ve
Hence minimum
Now {tex}s = 4\pi {r^2}{/tex}
We have {tex}s = \pi rl + \pi {r^2}{/tex}
{tex}4\pi {r^2} = \pi rl + \pi {r^2}{/tex}
{tex}\Rightarrow{/tex} {tex}3\pi {r^2} = \pi rl{/tex}
{tex}\Rightarrow{/tex} 3 r = l
{tex}\Rightarrow{/tex} {tex}\frac{r}{l} = \frac{1}{3}{/tex}
{tex}\Rightarrow{/tex} {tex}\sin \alpha = \frac{1}{3}{/tex}
{tex}\therefore{/tex} {tex}\alpha = {\sin ^{ – 1}}\left( {\frac{1}{3}} \right){/tex}

## Chapter Wise Important Questions Class 12 Maths Part I and Part II

### Test Generator

Create question paper PDF and online tests with your own name & logo in minutes.

### myCBSEguide

Question Bank, Mock Tests, Exam Papers, NCERT Solutions, Sample Papers, Notes